PERAN TINDAK TUTUR DALAM MEMAINKAN KATA HEAN NIDAN DI DOJO RAUDHTUL JANNAH: The Role of Speech Acts in Perfoming “Kata Hean Nidan” at Raudhtul Jannah's Dojo - Mhd. Johan; Winda Evyanto; Gaguk Rudianto; Robby Satria; Zia Hisni Mubarak; Yunisa Oktavia; Afriana; Muhammad Imam Akbar Hairi (ASOSIASI IDEBAHASA KEPRI, 2023)
The purpose of this service is to see and follow up on the abilities of the kohais of the Raudhatul Jannah dojo in order to achieve better achievements. Speech act is something that is needed in karate practice, in this case it is not speech to convey messages that need to be carried out by kohai-kohai in practice. If the kohais don't understand the speech conveyed by the trainer, the communication between the trainer and the kohai cannot work. Karate is a martial art where a trainer has a target in the training. The failure or success of the coach can be seen from the success of his students. Kohai-kohai dojo Raudhatul Jannah still cannot compete with athletes from around Batam because their training schedule is very minimal. The method used in this service is for the servant to directly train and improve the kohai-kohai technique and get results that still need to be repaired and trained.